Relationship between Cryptosporidium parvum in Water And Diarrheal Infections at Wasit Province - Abdulsada A. Rahi; Safa K. Alwan (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present study aimed to identify the relationship between Cryptosporidium parvum in water and diarrhealinfections at Wasit province. One hundred stool samples were collected (male and female) from suspecteddiarrheal patients of parasitic infection who attended to Al-kut hospital and Al-karamah teaching hospitalat Wasit province and fifty water samples were collected from different points at Dijlah river; Householdwater supply and Kut Liquid water during the period from October 2020 to April 2021.The investigation ofoocysts of the Cryptosporidium parvum parasite carried out by staining with modified Ziel Neelson method.The results of our study revealed that 60(60%) was positive for C.paravum. The age group (1-5) monthsshowed the highest 12(12%) prevalence rate while the lowest prevalence was in patient with age group(>20) months reached to 1(1%).